2021
DOI: 10.3390/ijerph18179168
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Physical Activity, Sitting Time, and Time Spent Outdoors with Mental Health during the First COVID-19 Lock Down in Austria

Abstract: Measures implemented to reduce the spread of SARS-CoV-2 have resulted in a decrease in physical activity (PA) while sedentary behaviour increased. The aim of the present study was to explore associations between PA and mental health in Austria during COVID-19 social restrictions. In this web-based cross-sectional study (April–May 2020) moderate-to-vigorous physical activity (MVPA), sitting time, and time spent outdoors were self-reported before and during self-isolation. Mental well-being was assessed with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 46 publications
3
44
0
2
Order By: Relevance
“…Results of this study showed that physical activity decreased in Austria during the COVID-19 pandemic, as female and male participants spent less time on exercising. Similar results were found in earlier studies conducted in the beginning of the crisis [ 12 , 14 , 18 ]. Our results revealed that decreased exercising indoors mostly applied to public sport facilities (i.e., fitness centers or sports clubs), as home exercising gained popularity during the crisis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Results of this study showed that physical activity decreased in Austria during the COVID-19 pandemic, as female and male participants spent less time on exercising. Similar results were found in earlier studies conducted in the beginning of the crisis [ 12 , 14 , 18 ]. Our results revealed that decreased exercising indoors mostly applied to public sport facilities (i.e., fitness centers or sports clubs), as home exercising gained popularity during the crisis.…”
Section: Discussionsupporting
confidence: 92%
“…During the pandemic, the majority of the participants considered health and physical activity as important motivational factors for visiting outdoor areas. These findings are not surprising, as prior studies suggested increased importance of nature for regular physical activity during the COVID-19 pandemic [ 18 , 26 , 36 ]. Consequently, the value of recreational outdoor activities has presumable increased during the crisis.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations